Métodos quantitativos aplicados na gestão de empreendimento econômico solidário, em Tomé Açu-PA - RODRIGUES, Ellen Cristina Nabiça (2015)
Globalization has affected the world economy, high unemployment and generated impact on the living conditions of people in big cities and in rural areas, especially in developing countries. In this logic, Solidarity Economy Enterprises (SEE) are presented as a solution to farmers to ensure source of income, improvement in quality of life and attachment to the field. The collective organization of farmers in associations emerges as facing factor increase productivity, reach new markets, income, raise self-esteem of the associated producers and enable economic organization. The farmers of the community of Santa Luzia, the city of Tome Acu - PA organized collectively in an Solidarity Economy Enterprises (SEE), aiming to benefit the production of their agroforestry systems (AFS's), adding value and getting associatively access markets as Food Acquisition Program (FAP) and the National School Feeding Programme (NSFP), with the supply of frozen fruit pulp. In this sense, this thesis analyzes the aspects that make up the general framework of activities undertaken by SEE, through a study of the influence of the production chain of acai in income generation of farmers, through the influence of quality control in processing fruit pulp, and the importance of the degree of satisfaction associated producer as part of a collective organization and ending with proposing a management tool to optimize the processing of agro-industry as a strategy for decision making and improving competitiveness, contributing to the effective planning pulp production cupuaçu and açaí. The AFS’s contributed to a more sustainable local development, reducing the landscape changes of pressure that has today with the advancement of a new monoculture that is the palm. The biggest obstacle to SEE study was the lack of resources for large investments as structural adequacy that committed the deadlock agribusiness and consequently affecting the income and satisfaction of members. The dimensions determining the satisfaction of the associated producers are correlated with living conditions, satisfaction as an associate, income source and migration. Through operational research tool, was poosível get a production plan to minimize production costs. The possession of this tool to support the management of family agribusiness makes for a smart and proper choice of the best and most appropriate way to produce according to the desired demand for enterprise.